Mit üzen a múlt? Gondolatok a II. világháborút követő gyermekvédelmi reformtörekvésekről és a gyermekköztársaságokról - Korinek, Beáta Zsófia (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
One of the greatest global traumas of the 20th century was World War II. Millions of children have become abandoned. In this extreme life situation, professionals, responsible adults and reform educators felt it their job to embrace and save them. They worked to ensure that orphaned children could continue their lives without a family background. In my study, I present the importance of action instead of ‘bystander effect’ and the importance of ‘becoming capable’ and ‘empowerment’ instead of simple care for children in need through a couple of examples of so-called children’s republics, primarily Father Flanagen’s Boys Town and Gábor Sztehlo’s Gaudiopolis.